PENGARUH WAKTU MASERASI TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN PEGAGAN (Centella asiatica (L.) Urban) - Trisna Rahayu, Ni Komang; Mayun Permana, I Dewa Gede; Diah Puspawati, GA. Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This research aimed to determine the effect of maceration time on the antioxidant activity of pegagan leaf extract and to determine the best maceration time with highest antioxidant activity of pegagan leaf extract. The experimental design used was Completely Randomized Design with maceration time duration there were 18, 24, 30, 36, 42, and 48 hours. All of the treatment repeated three times to obtained 18 units of experiments. The data analyzed by analyze of variance, if the treatment had a significant effect followed by The Duncan Test. The results showed that the maceration time treatment had a significant effect on yield, total phenolik, total flavonoid, total tannin and antioxidant activity of pegagan leaf extract. The 24 hour maceration time was the best treatment with antioxidant activity 66.67%, IC50 632.82 ppm, a yield of 24.30%, a total phenolik of 57.85 mgGAE / g, a total flavonoid of 105.28 mgQE / g. total tannin 54.09 mgTAE / g.